Functional magnetic resonance imaging (fMRI) response to alcohol pictures predicts subsequent transition to heavy drinking in college students. (19th January 2014) - Dager, Alecia D.; Anderson, Beth M.; Rosen, Rivkah; Khadka, Sabin; Sawyer, Broderick; Jiantonio‐Kelly, Rachel E.; Austad, Carol S.; Raskin, Sarah A.; Tennen, Howard; Wood, Rebecca M.; Fallahi, Carolyn R.; Pearlson, Godfrey D.
Abstract Background and Aims Young adults show the highest rates of escalating drinking, yet the neural risk mechanisms remain unclear. Heavy drinkers show variant functional magnetic resonance imaging (fMRI) blood oxygen level‐dependent (BOLD) response to alcohol cues, which may presage increasing drinking. In this longitudinal study, we ascertained whether BOLD response to alcohol pictures predicted subsequent heavy drinking among college students. Methods Participants were 43 18–21‐year‐olds in the United States who underwent BOLD scanning and completed monthly substance use surveys over the following year. Participants were categorized according to baseline and follow‐up drinking into 13 continuously moderate drinkers, 16 continuously heavy drinkers and 14 transitioners who drank moderately at baseline but heavily by follow‐up. During fMRI scanning at baseline, participants viewed alcohol and matched non‐alcohol beverage images. Results We observed group differences in alcohol cue‐elicited BOLD response in bilateral caudate, orbitofrontal cortex, medial frontal cortex/anterior cingulate and left insula (clusters > 2619 ml, voxelwise F(2, 40) > 3.23, P < 0.05, whole‐brain corrected P < 0.05), where transitioners hyperactivated compared with moderate and heavy drinkers (all Tukey P < 0.05). Exploratory factor analysis revealed a single brain network differentiating those who subsequently increased drinking. Exploratory regressions showed that, compared with other risk factors (e.g. alcoholism family history, impulsivity), BOLD response best predicted escalating drinking amount and alcohol‐related problems. Conclusions Neural response to pictures of alcohol is substantially enhanced among United States college students who subsequently escalate drinking. Greater cue‐reactivity is associated with larger increases in drinking and alcohol‐related problems, regardless of other baseline factors. Thus, neural cue‐reactivity could uniquely facilitate identifying individuals at greatest risk for future problematic drinking.